THE APPLICATION OF BRAIN GYM IN IMPROVING COGNITIVE FUNCTION IN ELDERLY WITH DEMENTIA - Syukriyah Syukriyah (Universitas Bina Bangsa Getsempena, 2024)
Dementia is an irreversible progressive brain disorder that slowly makes sufferers experience a decrease in memory, thinking, behavior, and the ability to carry out daily activities, where symptoms usually appear at the age of 60 years and above. The application of brain exercises is one of the interventions in improving cognitive function in the elderly with dementia. This study aims to improve cognitive function in the elderly with dementia. This type of research is descriptive using a case study approach method. Data collection techniques in this study were interviews and observations. This study uses inform consent sheets, assessment sheets, music and observation sheets. Respondents in this study were two elderly people with dementia with age criteria of 60 years and over. The results showed that the interpretation before the intervention in both subjects was subject I the result was 20 and subject II the result was 19. Interpretation after intervention subject I became 22 and subject II became 23. This study proves that brain exercises can improve cognitive function in the elderly with dementia. It is hoped that brain gymnastics can be used as one of the interventions to reduce cognitive function in the elderly with dementia.